Corporal education and school dropout: a forgotten issue in the innovations of revue EP.S and official discourses (1981-2020)? (Práxis Educativa, 2023)
When the French Ministry of National Education was reintegrated in 1981, Physical Education (PE) actors were assigned new missions. This article examines the participation of PE actors in a mission which surpasses disciplinary reflection: fighting against dropping out of school. Since 1981, a descriptive analysis of the “revue EP.S”’s articles was conducted and was enriched by a statistical analysis of textual data from the main curricular discipline. Only 6 articles focus on the problem of school drop-out, and no disciplinary text links school drop-out to compulsory education in PE. These results showed the problem of dropping out of school remains a school mission forgotten by PE stakeholders during this period. Since 1981, PE actors seem to have been anchored in a disciplinary logic that places limitations on the involvement of its actors in broader school issues. Implications questioned both the contribution of PE knowledge to school missions over the past forty years and the ability of those involved in a physical discipline to respond to current school challenges.Keywords: Physical Education. School drop-out. School perseverance.